Social sustainability practices in the supply chain of Indian manufacturing industries. (2015) - V., Mani.; Agrawal, Rajat; Sharma, Vinay
Though the sustainability addresses predominantly on environmental concerns for many decades, the focus on social sustainability in the supply chain was explored less. In developing countries, social sustainability is gaining momentum recently, in the wake of increasing social issues flagged by social organisations. This research on social sustainability unearths the social sustainability practices adopted by two different manufacturing companies, from two different domains that include automobile and fast moving consumer goods (FMCG) industry. In this research, comparative case study methodology is employed, that includes identification of social dimensions which are specific to manufacturing industries, and comparative analysis of various practices adopted by two different manufacturing companies. Major findings imply similarities and differences between companies that can lead to different approaches to sustainability. There were significant differences in the sustainable practices between FMCG and Automobile companies, given their different dynamics. However, all the practices lead to social sustainability in the Indian continent. This research helps the supply chain managers and decision makers who are involved in operations to understand different practices and their impact on different industries, which will act as a guiding tool for decision making.